2017
DOI: 10.1515/ata-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic Conditions on Differences in Thermo-Technical Properties of Organic Bedding in Laboratory Testing

Abstract: The aim of this experiment was to analyse the influence of climatic factors on the thermal performance of separated liquid manure. The samples of organic bedding were collected from the lying area of dairy housing and preparatory store. The measurement of properties of recycled manure solids (RMS) was carried out in laboratory conditions. Samples were examined with determining the temperature effect on the thermal conductivity λ of 'dry' separated liquid manure (with a dry matter content of 60%) and 'wet' liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is a very important indicator of the quality of the barn environment. It does combine the effect of the air temperature and the relative humidity [ 9 , 12 , 13 , 14 , 15 , 16 ]. The THI model does not take into account other environmental factors, such as the air velocity or the solar radiation intensity; the THI is still considered to be an excellent indicator of stressful climatic conditions [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a very important indicator of the quality of the barn environment. It does combine the effect of the air temperature and the relative humidity [ 9 , 12 , 13 , 14 , 15 , 16 ]. The THI model does not take into account other environmental factors, such as the air velocity or the solar radiation intensity; the THI is still considered to be an excellent indicator of stressful climatic conditions [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It involves the heat flow from the skin down a thermal gradient to a surface that has a lower temperature in summer (Ortiz et al, 2014). When a cow lies on water mattress, mattress surface temperature is cooler than the cow's skin, which allows transfer the heat from the body into the water inside the mattress (Lendelová et al, 2017). In practice, water mattress surface temperature provides a cooler lying surface before the cow lies on it.…”
Section: Results and Discussion Michaela Némethová Et Almentioning
confidence: 99%
“…There is a wide range of possibilities for dairy housing (Kull et al, 2017). The dairy cattle spend most of the time lying and the surface on which they lie has already been described by multiple researchers (Tucker et al, 2003;Lendelová et al, 2009;Kull et al, 2017) as affecting the dairy cows in several ways. Cattle at dairy usually lie on straw; sawdust; sand; mattresses filled with recycled material; mattresses filled with rubber; and water mattresses.…”
mentioning
confidence: 99%
“…The difference in lying preference in Experiments 1 and 2 indicated that the lying CI of WSs is greater than that of sand in a temperate climate and this is consistent with previous studies [ 22 ]. The difference in thermal conductivity between sand and wood shavings may affect thermal comfort during lying and hence usage of the lying area [ 23 , 24 ]. In addition, WSs may have a greater bearing capacity for cattle’s feet and body weight than sand.…”
Section: Discussionmentioning
confidence: 99%